Comparison of EuroSCORE II and the society of thoracic surgeons risk score for predicting 30-day mortality among Bangladeshi patients undergoing isolated coronary artery bypass grafting at a single center - Al-Nimari, M. Zafar; Pal, Nittyananda; Chowdhury, Dewan Iftakher Raza; Salahuddin, Ahmad Pear; Islam, Mohammad Azizul; Sharma, Satyajit; Saha, Oindril; Azim, Anowarul (International Surgery Journal, 2025)
Background: There are many risk stratification models have been developed to predict short-term morbidity and mortality after cardiac surgery. This study compared the European system for cardiac operative risk evaluation (EuroSCORE) II and the society of thoracic surgeons (STS) risk score to predict 30-days mortality in patients undergoing isolated coronary artery bypass grafting (CABG). Methods: This comparative cross-sectional study was carried out in department of cardiac surgery of national heart foundation hospital and research institute, Dhaka, from September 2020 to August 2022. Ethical approval was taken from the institutional review board of NHFH and RI. Following informed written consent, preoperative EuroSCORE II and STS risk score were assessed among total of 500 patients who underwent isolated CABG. Patients were followed up after 30-days to see the outcome. Data were analyzed by SPSS-26. Risk model comparison was done by calculating Z score of area under receiver operator curves, unpaired t test and McNemar’s test. P<0.05 was considered statistically significant. Results: Mean±SD age of the study was 60.20±7.46 (SD) years. Maximum patients were male (81.8%), overweight (55.6%), hypertensive (63.6%) and diabetic (44.2%). Mean EuroSCORE II and STS risk score of all patients was 2.51±1.98 and 2.42±1.86, respectively. Overall, 30-days mortality was 1.4% (n=7). Both EuroSCORE II and STS risk score had similar capability in predicting 30-days mortality among isolated CABG patients with excellent accuracy (as area under curve was 0.936 and 0.922, respectively). Conclusions: Both EuroSCORE II and STS risk score are similarly effective to predict 30-days mortality in isolated CABG patients.